Analyzing the capacitor ignition process in the hybrid ignition system - Do , Van Dung; Do , Quoc Am; Nguyen , Tan Ngoc (Journal of Technical Education Science, 2020)
This paper analyzed the capacitor-discharged process in the hybrid ignition system. The analyzed factor is the primary current and self-induced emf in the capacitor-discharged stage of the hybrid ignition system. Matlab was used to simulate the primary current and self – induced emf. The analyzed and simulation results help conclude the equation of the primary current and self-induced emf suitable with the actual process in the hybrid ignition system